2021
DOI: 10.1002/jlb.5hi0321-179rr
|View full text |Cite
|
Sign up to set email alerts
|

Specific innate immune cells uptake fetal antigen and display homeostatic phenotypes in the maternal circulation

Abstract: Pregnancy represents a period when the mother undergoes significant immunological changes to promote tolerance of the fetal semi‐allograft. Such tolerance results from the exposure of the maternal immune system to fetal antigens (Ags), a process that has been widely investigated at the maternal‐fetal interface and in the adjacent draining lymph nodes. However, the peripheral mechanisms of maternal‐fetal crosstalk are poorly understood. Herein, we hypothesized that specific innate immune cells interact with fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 163 publications
(317 reference statements)
0
5
0
Order By: Relevance
“…[102][103][104][105] Indeed, prior studies in mice have demonstrated that innate immune cells in the periphery interact with fetal antigens throughout pregnancy, which was replicated in vitro by using human innate immune cells from the second and third trimesters. 103 Furthermore, cell-free fetal DNA (cffDNA) concentrations have been shown to increase in the maternal circulation in late gestation, which coincides with a pro-inflammatory shift in maternal immunity prior to parturition. [106][107][108][109] Specifically, cffDNA has been demonstrated to stimulate a monocyte response in the third trimester capable of activating bystander T cells.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…[102][103][104][105] Indeed, prior studies in mice have demonstrated that innate immune cells in the periphery interact with fetal antigens throughout pregnancy, which was replicated in vitro by using human innate immune cells from the second and third trimesters. 103 Furthermore, cell-free fetal DNA (cffDNA) concentrations have been shown to increase in the maternal circulation in late gestation, which coincides with a pro-inflammatory shift in maternal immunity prior to parturition. [106][107][108][109] Specifically, cffDNA has been demonstrated to stimulate a monocyte response in the third trimester capable of activating bystander T cells.…”
Section: Discussionmentioning
confidence: 89%
“…86 Thus, the co-expression of CD69 and PD-1 likely indicates prolonged T-cell activation, as would be expected following chronic antigen exposure. Considering the presence of fetal antigens in the maternal circulation, 53,102,103 it is tempting to suggest that the increased proportion of CD4 + CD69 + PD-1 + T cells in pregnant women may reflect repeated exposure to such fetal antigens. [102][103][104][105] Indeed, prior studies in mice have demonstrated that innate immune cells in the periphery interact with fetal antigens throughout pregnancy, which was replicated in vitro by using human innate immune cells from the second and third trimesters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maternal monocyte population detected in the placental tissues likely represents circulating cells present in the intervillous space ( 121 , 122 ). Previous reports have noted the enhanced activation of maternal circulating monocytes in the context of labor ( 93 , 123 , 124 ), likely driven by signals derived from the placental tissues ( 125 ), because such innate immune cells display up-regulated expression of activation markers and can phagocytose placenta-derived particles ( 126 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy has been associated with increased expression of activation markers in peripheral innate immune cells [ 11 , 40 , 59 , 60 ], which is postulated to result from gestational factors such as the presence of placental microparticles and fetal cells in the maternal circulation [ 41 , 61 63 ]. Accordingly, a significant shift has been reported in the frequency of monocyte subsets from classical to intermediate, the latter displaying the surface signals of activation and differentiation in human pregnancy [ 64 ] and in an animal model [ 65 ].…”
Section: Discussionmentioning
confidence: 99%